Synthesis of Coal-Fly-Ash Geopolymer for Sustainable Construction Material: Optimisation of Formulation and Environmental Characterisation - Akhmad Syafi’i; Sherina Prahitaningtyas; Sukma Hendrian; Malik Rismanto; Hilyah Farhany Faradilla (Publikasi Indonesia, 2025)
This study investigates the synthesis of geopolymer materials derived from Indonesian coal fly ash as a sustainable alternative to conventional cement. The research aims to optimize geopolymer synthesis parameters and evaluate the environmental performance of the resulting material. Using a laboratory experimental approach supported by qualitative analysis, the study examined the effects of key parameters including alkali activator concentration, Si/Al ratio, and curing temperature on geopolymer formation. Experimental observations and supporting expert insights indicated that optimal geopolymerization occurred at an activator concentration of 10–12 M NaOH, a Si/Al ratio of approximately 2.0–2.5, and a curing temperature of around 60°C, producing dense and structurally stable materials. Environmental characterization revealed that heavy-metal leaching levels of Pb, Cd, and Cr were significantly below regulatory thresholds, indicating strong immobilization within the geopolymeric matrix. In addition, the utilization of coal fly ash contributes to reducing industrial waste accumulation and lowering carbon emissions associated with cement production. These findings demonstrate that coal-fly-ash–based geopolymers possess strong potential as sustainable construction materials. However, large-scale implementation requires standardized technical guidelines, supportive regulatory frameworks, and collaboration between research institutions and industry stakeholders.